(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
An uncommon case of chondrosarcoma involving frontal sinus is presented. Pertinent literature is reviewed to emphasize the management of this tumor at unusual site. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10425 Bangladesh J Otorhinolaryngol 2012; 18(1): 81-83